2007
DOI: 10.1016/j.febslet.2007.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uncoupling protein‐1 expression on 3T3‐L1 adipocyte gene expression

Abstract: The mitochondrial respiratory uncoupling protein 1 (UCP1) partially uncouples substrate oxidation and oxidative phosphorylation to promote the dissipation of cellular biochemical energy as heat in brown adipose tissue. We have recently shown that expression of UCP1 in 3T3-L1 white adipocytes reduces the accumulation of triglycerides. Here, we investigated the molecular basis underlying UCP1 expression in 3T3-L1 adipocytes. Gene expression data showed that forced UCP1 expression down-regulated several energy me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In general, this phenotype suggests that the main function of respiratory uncoupling and uncoupling proteins (UCPs) in white adipocytes might be the attenuation of lipid accumulation, mainly due to a decrease in FA synthesis, increase of free fatty acid (FFA) β-oxidation, impaired noradrenaline-stimulated lipolysis and modulation of hormonal control of lipid metabolism as well as the stimulation of mitochondrial biogenesis, UCP-2 over-expression and Gαi abundance modification (Rossmeisl et al, 2004). Additionally, the forced expression of UCP-1 in 3T3-L1 preadipocytes limits the differentiation efficiency by increasing protein stability and decreasing expression of genes encoding proteins involved in energy-consuming processes (Senocak et al, 2007). Although there is good evidence in favour of a major role for mitochondrial uncoupling in lipid metabolism leading to a significant decrease in TG content of adipocytes, the impact on adipogenic markers and effectors is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In general, this phenotype suggests that the main function of respiratory uncoupling and uncoupling proteins (UCPs) in white adipocytes might be the attenuation of lipid accumulation, mainly due to a decrease in FA synthesis, increase of free fatty acid (FFA) β-oxidation, impaired noradrenaline-stimulated lipolysis and modulation of hormonal control of lipid metabolism as well as the stimulation of mitochondrial biogenesis, UCP-2 over-expression and Gαi abundance modification (Rossmeisl et al, 2004). Additionally, the forced expression of UCP-1 in 3T3-L1 preadipocytes limits the differentiation efficiency by increasing protein stability and decreasing expression of genes encoding proteins involved in energy-consuming processes (Senocak et al, 2007). Although there is good evidence in favour of a major role for mitochondrial uncoupling in lipid metabolism leading to a significant decrease in TG content of adipocytes, the impact on adipogenic markers and effectors is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, expression of uncoupling protein-1 (UCP1) in white and brown adipose cells of aP2-Ucp1 mice has been reported to lower body weight, to change fat distribution in the body (enlarged gonadal fat and decreased subcutaneous fat), and to prevent development of genetic or dietary obesity (38,39,41). Mitochondrial uncoupling induced by pharmacological molecules such as FCCP or ectopic UCP1 expression also leads to 3T3-L1 adipocyte dedifferentiation controlled by modifications in the expression of many genes (65,67,73).…”
mentioning
confidence: 99%
“…In other words, uncoupling increases cellular metabolic demand since uncoupling OXPHOS lowers ATP production and increases the demand for reducing equivalents to restore/maintain mitochondrial membrane potential, thereby increasing substrate catabolism, which would theoretically decrease triglyceride (TG) stores in adipocytes. Indeed, although mitochondrial dysfunction could represent a major cause of lipid metabolism disorders and pathological triglyceride accumulation in several cell lines (50, 75), we and others have shown that mitochondrial uncoupling in adipocytes triggers lipolysis, limits fatty acid synthesis, and leads to a reduction in TG content (40,61,65,67,73), a characteristic also found during the "dedifferentiation" of adipocytes (86).Mature adipocyte dedifferentiation has been defined as the acquisition of a more primitive phenotype and gain of cell proliferative ability (48) as well as a reduction in TG content in adipocytes (29,52). In this study, we will refer to adipocyte dedifferentiation as a reduction of TG content and downregulation of adipogenic markers and effectors.…”
mentioning
confidence: 99%
“…Furthermore, expression of ectopic UCP1 resulted in reduced expression of genes characteristic of differentiated energy-storing adipocytes, such as peroxisome proliferator-activated receptor gamma (PPARc) and aP2 , in analogy with the induction of ''fat burning adipocytes'' in response to leptin treatment in rats (Zhou et al 1999). In accordance, mitochondrial uncoupling in adipocytes in vitro led to lower intracellular ATP concentrations (Yamada et al 2006;Si et al 2009), up-regulation of glycolysis and mitochondrial biogenesis, and down-regulation of energyconsuming pathways such as fatty acid synthesis (Rossmeisl et al 2000;Si et al 2009;Senocak et al 2007), while lactate production was increased (Rossmeisl et al 2000; ) N D Decreased (Ishigaki et al 2005) Mitochondrial biogenesis and/or content Increased (Rossmeisl et al 2002) Content decreased (Han et al 2004) N D Mitochondrial ROS production ND Reduced (Keipert et al 2010) N D Cellular ATP levels Decreased Yamada et al 2006); increased AMP/ATP ratio Unchanged (Li et al 2000) or decreased (Li et al 2000;Couplan et al 2002;Han et al 2004 Rossmeisl et al, unpublished) suggested an upregulation of lipid catabolism in SM of high-fat diet-fed mice in response to the transgenic UCP1 expression in WAT, which is also associated with hypolipidemic effects, especially under fasted conditions. The effect of UCP1 expression on SM phenotype was studied in detail by Couplan et al (2002), who reported a fiber type switch from fast glycolytic fibers to slow oxidative fibers in gastrocnemius and plantaris muscle accompanied by a reduced muscle mass.…”
Section: Metabolic Effects Of Ectopic Ucp1 At Cellular and Tissue Levelsmentioning
confidence: 95%
“…There are also reports on the forced expression of UCP1 in 3T3-L1 cells, a murine preadipocyte cell line (Yamada et al 2006;Si et al 2007Si et al , 2009Senocak et al 2007). …”
Section: White Adipose Tissuementioning
confidence: 99%